The Determination of Aromatic Character of Several Local Rice Varieties using Phenotypic Analysis and Molecular DNA - Fanata, Wahyu Indra Duwi; Husna, Syafira Fatihatul (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2021)
The pandan scent in aromatic rice has been known as the result of 8 bp deletions and 3 Single Nucleotide Polymorphisms (SNPS) in BADH2 gene, which produce non-functional betaine aldehyde dehydrogenase (BADH) enzyme. Several DNA markers for aromatic character based on mutation in BADH2 gene have been developed. In our experiment, we analysed the presence of aromatic character in four local rice variety such as Merah Wangi, Pendok, Genjah Arum, and Mentik Wangi Susu using KOH method and DNA molecular method using three DNA markers to detect mutation that responsible for the development of aromatic character. Phenotype analysis using KOH method showed that Merah Wangi, Genjah Arum, and Mentik Wangi Susu produce pandan scents. PCR analysis using Bradbury and Badex7-5, and RM223 markers showed the presence of BADH2 mutation in Merah Wangi and Mentik Wangi Susu, whereas Pendok and Genjah Arum did not show BADH2 mutation using those used three markers. Our results indicate that among four investigated local rice, only Merah Wangi and Mentik Wangi Susu are categorized as aromatic rice whereas Pendok and Genjah Arum are non-aromatic.Keywords: genetic analysis, aromatic rice, specific markers, genetic mutation.